Are structural parameters stable in Malaysia? Pre- and post-crisis analysis - Fathin Faizah Said,; Zulkefly Abdul Karim, (Penerbit Universiti Kebangsaan Malaysia, 2016)
This research examines whether structural parameters of new keynesian models are stable in Malaysia. We imposed the structural restrictions as in DSGE models suggested by Smets and Wouters (2003) and Wickens (2011). We then estimated whether the 2007 financial crisis changes structural parameters by using structural VAR estimation. Our parameters estimates are significant and correctly signed. This empirical finding has found that the structural parameters are not stable after the 2007 financial crisis, for employment, rate of return on loans and policy rate. However, the effects are little on the real variables such as output, investment, consumption and price level. In addition, unexpected change of demand in the non-bank private sector has puzzled the rate of return on loans after the economic crisis compared with before the economic crisis. The monetary policy shocks have given a fluctuation effect on the rate of return on loans and employment after the economic crisis.